2008
DOI: 10.1152/ajpheart.00299.2008
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of extracellular heat shock cognate protein 70 in the myocardial inflammatory response and cardiac dysfunction after global ischemia-reperfusion

Abstract: Critical role of extracellular heat shock cognate protein 70 in the myocardial inflammatory response and cardiac dysfunction after global ischemia-reperfusion. Am J Physiol Heart Circ Physiol 294: H2805-H2813, 2008. First published April 25, 2008 doi:10.1152/ajpheart.00299.2008.-Previous studies showed that Toll-like receptor 4 (TLR4) modulates the myocardial inflammatory response to ischemia-reperfusion injury, and we recently found that cytokines link TLR4 to postischemic cardiac dysfunction. Although TLR4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 36 publications
2
69
0
2
Order By: Relevance
“…45 One report using global ischemia-reperfusion in an isolated heart model suggested that heat shock cognate protein 70 (90% homologous to HSP70) is acutely induced by ischemia in cardiomyocytes and is secreted and rapidly detected in coronary effluent. 46 Inhibitory antibody to heat shock cognate protein 70 was able to attenuate ischemia-induced cardiac dysfunction. 46 Our results add to these observations by demonstrating that extracellular HSP70 directly decreased cardiomyocyte contractility and increased cell death; an effect that depended on the signalling pathway defined by TLR2, MyD88, and NFκB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 One report using global ischemia-reperfusion in an isolated heart model suggested that heat shock cognate protein 70 (90% homologous to HSP70) is acutely induced by ischemia in cardiomyocytes and is secreted and rapidly detected in coronary effluent. 46 Inhibitory antibody to heat shock cognate protein 70 was able to attenuate ischemia-induced cardiac dysfunction. 46 Our results add to these observations by demonstrating that extracellular HSP70 directly decreased cardiomyocyte contractility and increased cell death; an effect that depended on the signalling pathway defined by TLR2, MyD88, and NFκB.…”
Section: Discussionmentioning
confidence: 99%
“…46 Inhibitory antibody to heat shock cognate protein 70 was able to attenuate ischemia-induced cardiac dysfunction. 46 Our results add to these observations by demonstrating that extracellular HSP70 directly decreased cardiomyocyte contractility and increased cell death; an effect that depended on the signalling pathway defined by TLR2, MyD88, and NFκB.…”
Section: Discussionmentioning
confidence: 99%
“…However, heat stress results in many cellular alterations which may also be involved. For example, when HSC70, the constitutively expressed member of the HSP70 family, was added to the buffer of an isolated heart system, myocardial TLR4 was activated and cardiac contractility, reduced (Zou et al 2008). Thus, other HSPs or perhaps other DAMP molecules such as uric acid, which is known to be increased following heat stress, could also play a role (Shi et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, extracellular inducible hsp70 has been reported to increase activation of hepatocytes following ischemia-reperfusion injury (40) and to induce airway inflammatory responses (41). Importantly, extracellular hsc70 was shown to play a critical role in myocardial inflammation following injury (42). In addition to release during cellular necrosis, there are now recognized to be active, stress-induced secretion mechanisms for hsp, including hsc70 (43,44).…”
Section: Discussionmentioning
confidence: 99%